Biochemical composition of a smokeless tobacco product (NASWAR) used in Pakistan - Muhammad Saeed; Muhammad Asad; Muhammad Shahzad; Muhammad Akram; Zohaib Khan (Journal of King Saud University: Science, 2024)
Objectives: The objective of the study was to investigate the constituents of the most commonly consumed naswar brands from Khyber Pakhtunkhwa, Pakistan. Methods: A total of 14 most-sold brands of naswar, two from each division in KP were collected and analyzed by gas chromatography-mass spectrometry and inductively coupled plasma mass spectrometry to determine their organic and elemental composition respectively. In addition, pH, ash content, and aflatoxin assessment were also performed. Results: The average pH and ash content of all the test samples were 8.61 ± 0.271 and 18.94 ± 7.79 % respectively. Overall, the presence and concentration of the different constituents vary across the different naswar brands. GC–MS analysis identified 85 different organic compounds, the commonest being nicotine followed by glycerol tricaprylate and Di-n-octyl phthalate. Metal ions present in the highest concentration were iron (1146.84 ± 1050.31 mg/kg), tungsten (306.59 ± 494.82 mg/kg), and copper (288.95 ± 77.16 mg/kg). Aflatoxin B1 and B2 were the most common aflatoxins identified in naswar samples. Conclusions: Overall, naswar contains an array of organic, inorganic, toxic, and heavy metals and aflatoxin constituents with proven toxic and carcinogenic potential. Furthermore, high pH and nicotine contents make it highly addictive. There is an urgent need to enact and implement ST control policies to curb naswar use in Pakistan.